Advancing survivorship care through the National Cancer Survivorship Resource Center1. (19th March 2013) - Cowens‐Alvarado, Rebecca; Sharpe, Katherine; Pratt‐Chapman, Mandi; Willis, Anne; Gansler, Ted; Ganz, Patricia A.; Edge, Stephen B.; McCabe, Mary S.; Stein, Kevin
Abstract The National Cancer Survivorship Resource Center (The Survivorship Center) began in 2010 as a collaboration between the American Cancer Society and the George Washington University Cancer Institute and was funded by the Centers for Disease Control and Prevention. The Survivorship Center aims to improve the overall health and quality of life of posttreatment cancer survivors. One key to addressing the needs of this ever‐growing population is to develop clinical follow‐up care guidelines that emphasize not only the importance of surveillance for cancer recurrence, but also address the assessment and management of the physical and psychosocial long‐term and late effects that may result from having cancer and undergoing cancer treatment as well as highlight the importance of healthy behaviors that can reduce the risk of cancer recurrence, second primary cancers, and other chronic diseases. Currently, The Survivorship Center is coordinating the work of experts in oncology, primary care, and other health care professions to develop follow‐up care guidelines for 10 priority cancer sites. CA Cancer J Clin 2013. © 2013 American Cancer Society.